2020
DOI: 10.1177/0023830920952497
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental Frequency and Regional Variation in Lifou French

Abstract: This study presents two experiments aimed at investigating tune-to-text alignment and pitch scaling in Lifou French, a variety spoken by bilingual speakers of French and Drehu. Descriptions of New Caledonian French have focussed on language use of European descendants or the variety spoken in the urban region, neglecting emergent varieties spoken by the indigenous population in rural areas, like the island Lifou. Due to the reduced inventory of pitch accents, dialectal variation in French intonation has proved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…This means that apart from optional Drehu language classes all other subjects are taught in French and pupils follow the metropolitan school curriculum. Field work observations suggest that today almost all speakers, especially younger generations, are bilingual in French and Drehu (Torres, Fletcher & Wigglesworth 2020).…”
Section: Drehumentioning
confidence: 99%
“…This means that apart from optional Drehu language classes all other subjects are taught in French and pupils follow the metropolitan school curriculum. Field work observations suggest that today almost all speakers, especially younger generations, are bilingual in French and Drehu (Torres, Fletcher & Wigglesworth 2020).…”
Section: Drehumentioning
confidence: 99%
“…French additionally includes an optional phrase-initial pitch peak, often realised on the first syllable of the leftmost lexical word (for variation in initial pitch peak alignment, see e.g. Jun & Fougeron 2002;Welby 2006;Torres, Fletcher & Wigglesworth 2020). If no more than one pitch peak can be realised, as in shorter phrases, it is the final one that is preserved (Jun & Fougeron 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 shows a schematic representation of two F0 contours, one displaying continuous downstep (solid line), while the other shows downstep blocking (dashed line). For example, it has been shown that in Hexagonal and Lifou French, an intermediate phrase (ip) boundary is triggered when there is a major syntactic break between a noun and a verb phrase, leading to a blocking of downstep [4,11,12]. Similarly, studies about Tokyo Japanese have shown that a syntactic (left-)boundary blocks downstep [13,14].…”
Section: Introductionmentioning
confidence: 99%